Assessment of the health status of the Sidi R'Ghies forest, Oum El Bouaghi, north-east Algerian - Malika Rached Kanouni; Alia ZERROUKI; Maroua LAHMAR; Amina Beldjazia; Karima Kara; Labed Ababsa (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rached-Kanouni M, Zerrouki A, Lahmar M, Beldjazia A, Kara K, Ababsa. 2020. Assessment of the health status of the Sidi R'Ghies forest, Oum El Bouaghi, north-east Algerian. Biodiversitas 21: 1980-1988. In recent decades, the forest of Sidi R'Ghies has been degraded by human activity. The establishment of the state of the massif by a diagnosis on different forest plots is part of a project of monitoring and silvicultural management. The purpose of this study is to assess the health status of the Sidi R'Ghies forest. The methodology used was the visual assessment of the tree crown of the dominant species (i.e. Aleppo pine and holm oak) according to the protocols DEPEFEU, DEPERIS, and ICP Forests. These protocols were selected for adoption based on field observations and their applicability in record time. The results obtained indicate that the health status of the trees within the studied plots is declining. The DEPEFEU value index shows an average of 2.20 for Aleppo pine and 1.95 for holm oak while the DEPERIS has an average level of 4.56 in Aleppo pine and 3.07 in holm oak. ICP Forests has also contributed to providing clearer information on the consequences of this health situation by deducting an average visibility rate of 1.24 and 1.63; social status of 2.17 and 2.11 and competition of 1.71 and 2.49 for Aleppo pine and holm oak respectively. In general, the health status of the tree crown is average and almost adapted to the environmental conditions. In contrast, the carrying capacity of biodiversity is low and needs to be improved.